The silver spoon of solomon snow eaudiobook - Umansky, Kaye (Soloman Snow, 2017)
Nottinghamshire Book Award winner Kaye Umansky combines humor and a Dickensian atmosphere to bring young readers into the unlikely world of Solomon Snow. Solly's life stinks. He lives with Ma and Pa Scubbins in a rundown cottage outside of the village of Boring working as a delivery boy for their laundry service. But his luck soon changes when Ma lets slip a little secret-Solly was left on their doorstep as an infant with a silver spoon in his mouth. Solly sets out to find his spoon with the help of some ragamuffin friends he picks up along the way. But will Solly ever find his spoon and his real parents?